2013
DOI: 10.1287/opre.2013.1200
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Adaptive Network Flows

Abstract: We study network flow problems in an uncertain environment from the viewpoint of robust optimization. In contrast to previous work, we consider the case that the network parameters (e.g., capacities) are known and deterministic, but the network structure (e.g., nodes and arcs) is subject to uncertainty. In this paper, we study the robust and adaptive versions of the maximum flow problem and minimum cut problems in networks with node and arc failures, and establish structural and computational results. The adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 41 publications
2
82
0
1
Order By: Relevance
“…However, as soon as the interdictor is allowed to remove two arcs, the corresponding dual separation problem becomes NP -hard as was shown by Du and Chandrasekaran [11]. On the positive side, Bertsimas et al [7] building upon a generalization of the parametric LP used in [2], gave an LP-based approximation, in terms of the amount of flow removed by the interdictor in an optimal solution, for the case where the interdictor can remove any given number of arcs B I . More recently, Bertsimas et al [6] showed that the same flow also yields a 1 + (B I /2) 2 /(B I + 1)-approximation.…”
Section: Related Workmentioning
confidence: 98%
See 3 more Smart Citations
“…However, as soon as the interdictor is allowed to remove two arcs, the corresponding dual separation problem becomes NP -hard as was shown by Du and Chandrasekaran [11]. On the positive side, Bertsimas et al [7] building upon a generalization of the parametric LP used in [2], gave an LP-based approximation, in terms of the amount of flow removed by the interdictor in an optimal solution, for the case where the interdictor can remove any given number of arcs B I . More recently, Bertsimas et al [6] showed that the same flow also yields a 1 + (B I /2) 2 /(B I + 1)-approximation.…”
Section: Related Workmentioning
confidence: 98%
“…More recently, Bertsimas et al [6] showed that the same flow also yields a 1 + (B I /2) 2 /(B I + 1)-approximation. Formally, the model considered in [2,7,11] is defined for the uncertainty set Ω = {z ∈ {0, 1} A | 1 T z ≤ B I } and the flow player aims at solving max x∈X min z∈Ω val(x, z), where val(x, z) = P ∈P (1 − max e∈P z e )x P is the amount of flow x ∈ X that survives after the interdictor selects the scenario z ∈ Ω. A fractional version of this uncertainty set was proposed in [9]: Each arc has a cost c e for destroying the entire capacity on e and the interdictor is allowed to fractionally attack the capacities on the arcs, i. e., Ω = {z ∈ [0, 1] A | c T z ≤ B I }.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several alternative robustness models for flows have been proposed in different application contexts. Taking a less conservative approach, Bertsimas, Nasrabadi, and Stiller [3] and Matuschke, McCormick, and Oriolo [7] proposed different models of flows that can be rerouted after failures occur. Matuschke et al [8] investigated variants of robust flows in which an adversary can target individual flow paths and the network can be fortified against such attacks.…”
Section: Problem Definitionmentioning
confidence: 99%